Upaya Peningkatan Aktivitas Belajar Siswa pada Mata Pelajaran Matematika Melalui Penerapan Model Pembelajaran Interaktif pada Siswa Kelas XII-MIA-3 MAN 1 Kota Bima Tahun Pelajaran 2019/2020 - Siti Hadiah (Literasi: Jurnal Pendidikan Guru Indonesia, 2022)
This study aims to increase the activity of class XII-MIA-3 students. This type of research is Classroom Action Research conducted at MAN 1 Kota Bima with a total of 32 people. Research data was collected through observation sheets and field notes. The results showed that the percentage of students who achieved the Minimum Completeness Criteria (KKM) increased from 62% in cycle I to 75% in the cycle. during presentation. Students have worked well together in groups and are trying to help friends who have difficulty understanding the explanation of group material that appears. It can be concluded that learning mathematics can increase student activity through the application of an interactive learning model in class XII-MIA-3 students in the 2019/2020 academic year.